PENGARUH PERLAKUAN FISIK DAN KIMIA TERHADAP KECEPATAN DAN DAYA BERKECAMBAH BENIH BOTANI UBI KAYU F1 KETURUNAN TETUA BETINA UJ 3 - Utomo, Setyo Dwi; Nababan, Erick Mikhail Vialli; Pramono, Eko (JURNAL AGROTROPIKA, 2012)
The objective of this study was to evaluate the effect of pre-germination treatment (physical and chemical) on the percentage and rate of germination of the f1 true seed of cassava derived from female parent UJ 3. The study consisted of two experiment, i.e., Experiment I and II. The pre-germination treatments for the two units experiment were the same, i.e., scarification of seed coat using sand paper, seed coat puncture, submerging the seed in one of the following liquid: the solution of H 2SO4 0,001M for 5 minutes, solution of H2SO4 0,001M for 10 minutes, solution of KNO3 3% for 48 hours, and water for 48 hours. The treatments were also compared to control. After being treated, the seeds were germinated on moistened paper (UKDdp) for Experiment I and on the soil medium in polybag for Experiment II. The two units of experiment were arranged in randomized block design with three replications. Soil medium consisted of mixture of soil and compost (1:1). The results showed that percentage and the rate of germination of the treatment of submerging seed of H2SO4 0,001M for 5 minutes followed by germination on soil medium were high. The percentage and the rate of germination for the treatment were 96%; 10,5% per day respectively; whereas for the control were 78,7% dan 6,8% per day. Scarification using sand paper indicated the percentage and rate of germination were high. It can be concluded that pre-germination treatment by submerging on H2SO4 0,001M for 5 minutes was suitable for germinating true seeds of cassava cv. UJ 3. Key words: Dormancy, pre-germination, Manihot esculenta Crantz, scarification, seed viability